Density of gastropods and bivalves in coral reefs of Gili Island, Gresik Regency, Indonesia - Wahyunita, Fitrana; Fahmi, M. Yunan (Journal of Marine Resources and Coastal Management, 2024)
Gastropods and bivalves play a crucial role in the marine food web within coral reef ecosystems. This study aimed to identify gastropod and bivalve species and analyze their density in the coral reef ecosystem of Gili Island, Gresik Regency, East Java. Sampling was conducted using the belt transect method (100 meters in length and 5 meters in width), placed parallel to the shoreline at three selected research stations. A total of 19 individuals, representing two families of gastropods and bivalves, were identified. Species density ranged from 0.005 to 0.035 individuals/m², while relative density values ranged from 11% to 78%. The results indicate that the density and distribution of gastropods and bivalves in Gili Island waters are influenced by substrate types and water quality parameters.